Online tumor conference in the clinical management of gynecological cancer: experience from a pilot study in Germany. Issue 1 (1st January 2008) - Chekerov, R.; Denkert, C.; Boehmer, D.; Suesse, A.; Widing, A.; Ruhmland, B.; Giese, A.; Mustea, A.; Lichtenegger, W.; Sehouli, J.
Abstract : The concept of the online tumor conference was established in 2004 as a pilot project. We developed specific web-based software to organize and conduct online tumor board meetings of gynecologists, surgeons, radiologists, oncologists, and pathologists from different hospitals and gynecological practitioners, discussing individual patient's cases, defining therapy options, and exchanging clinical experience. Following a didactic approach, patient data are presented to the participants, with a special focus toward patient's preference and late toxicity from prior therapy. Then different national (eg, Arbeitsgemeinschaft Gynaekologische Onkologie, Deutsche Gesellschag fur Gynaekologic und Geburtshilfe) and international guidelines (eg, American Society of Clinical Oncology, National Cancer Institute), current study results based on literature review and open clinical trials are discussed. An individual diagnosis and therapy recommendation for each patient is reached by consensus. All protocols, guidelines, and publication data are upgraded and dispersed via Internet for all participants. In the period from December 2004 to August 2006, 39 tumor board conferences were performed with a total of 667 participants. One hundred forty-four patients' cases were presented, and 121 peer-reviewed second-opinions were sought. In an anonymous survey, 84% of the participants reported to be satisfied with the information content and 72% with the technical support. Overall 98% of the individual therapy recommendations were accepted and implemented. The tumor board conference presents an optimal possibility for extensive scientific discussions and exchange (92%) and improves advanced educational training (81%). In conclusion, the online tumor conference is feasible and represents a time-saving possibility for gynecological oncologist to receive a treatment recommendation based on the best available clinical and scientific evidence.